Resistensi Marapau terhadap Korporasi Untuk Melindungi Tanah - Umbu Deta, Krisharyanto (Satya Widya: Jurnal Studi Agama, 2021)
The establishment of a sugar cane plantation in East Sumba has evoked conflicts and resistance from the local people. The damage to the katoda (sites to perform rituals) portrays one of the other violations causing environmental, cultural, and social damages related to the manipulation of customary land and criminalization of local people. This paper aims to discuss this conflict by accentuating, and also promoting, the paradigm of indigenous religion as a tool to understand the resistance of the Marapu community to protect their land. Indigenous Religion Paradigm implies the inter-subjective relationship between human person and non-human person (nature) in the non-hierarchical cosmology, which carries the commitments of responsibility, ethics, and reciprocity. By using this perspective, this work shows the opposite perspectives of the partnership between the corporation and the local government concerning the economic considerations and Marapu community who maintains their inter-subjective cosmology as opposed to the modern economic view. The land is understood differently by each of them. While the former only grasps the monetary side of the land, the latter religiously perceives the land as sources of life for both human and non-human person and, therefore, protects their land as the commitment to be responsible, ethical, and reciprocal.